PERSEPSI WISATAWAN TERHADAP WISATA BUDAYA DI KOTA CIREBON (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2014)
This study aims to determine the perception of Travellers to Cultural Tourism of the city Cirebon In Knowing this Title Perception Travelers to Cultural Tourism the of city Cirebon. Methods In this small-scale applied research used descriptive method with quantitative approach, by describing the data, describe, and explain, which refers to the primary data and secondary data based on the fact that there are (actual), and then analyzed to produce a conclusion.